Evaluasi Anggaran Biaya Dan Pelaksanaan Pada Proyek Pembangunan Gedung Kantor Kecamatan Di Sragen (Studi Kasus Pembangunan Gedung Kantor Kecamatan Di Sragen - Murtono, Joko; , Ir. Sri Sunarjono, MT,PhD; , Ir. H. Muh. Nur Sahid, MM, MT (2016)
The purpose of this study are to know and analyze: a) planning and realization of work development in the subdistrict office building of Sragen Regency, b) the cost of implementing the construction of office buildings in Sragen Regency, c) scheduling implementation of projects development when there is a delay. Based on the results of research in previous chapters, it can be concluded that 1) implementation of the subdistrict office building development in Sragen Regency there is a delay work, 2) there is a difference between the realization with the cost of the execution plan of subdistrict office building in Sragen where the cost of implementation is lower than the cost of the plan, 3) based on the planning and implementation of development time of subdisctrics office building in Sragen Regency occurred rescheduling.